Hubungan Kondisi Sanitasi Lingkungan dan Perilaku Keluarga Terhadap Kejadian Penyakit Demam Berdarah Dengue di Wilayah Kerja Puskesmas Lepo-Lepo Kota Kendari Tahun 2024 - Fiqi Aprianto; Ramadhan Tosepu; La Ode Liaumin Azim; La Ode Muhammad Sety; Irma Irma; Jusniar Rusliafa (Program Studi S2 Kesehatan Masyarakat Universitas Halu Oleo, 2025)
This research focuses on environmental sanitation conditions and family behavior in relation to the incidence of dengue hemorrhagic fever (DHF) in the working area of Puskesmas Lepo-Lepo, Kendari City in 2024. The aim is to analyze the relationship between environmental sanitation conditions and family behavior. This study uses a quantitative method with a cross-sectional design and involves 364 respondents selected through proportional random sampling. The independent variables analyzed include environmental sanitation conditions and family behavior, while the dependent variable is the incidence of DHF. Data were collected through questionnaires that have been tested for validity and reliability and were analyzed using SPSS software with chi-square test. The results of the study show a significant relationship between environmental sanitation conditions and family behavior and the incidence of DHF. This study emphasizes the importance of improving environmental sanitation conditions and family behavior to reduce the incidence of DHF. These findings highlight the need for targeted interventions to enhance environmental sanitation and educate families in order to prevent the spread of DHF in the area. Thus, this research provides a significant contribution to dengue fever prevention efforts through community and environmental-based approaches